ANALISIS KESALAHAN MENULIS MAKALAH MAHASISWA PGSD UNIVERSITAS SULAWESI BARAT (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The purpose of this research is to identify spelling mistakes and grammatical errors in papers written by students. This research was conducted using a qualitative method that applies a descriptive approach. The research involved 3rd semester students in the PGSD study program. The number of papers analyzed were two student assignment papers. Data was collected by observation and documentation methods. Observations are carried out to see students' mistakes in writing papers, while documentation is papers that have been written by students. Data were analyzed using descriptive techniques. Descriptive analysis is used to describe student errors in writing papers. Indicators of mistakes in writing papers are the contents of the paper, grammar and writing techniques. The results showed that there were errors made by students in writing papers. It can be seen from the aspect of the content of the paper that students do not explain the contents of the paper completely, for example, in writing the background, the reasons for writing the paper are not explained in detail. In terms of grammatical aspects, there are still many errors in the use of punctuation, use of letters and use of words. Furthermore, in terms of the writing aspect, errors were still found in writing the list of references, and the procedure (ethics) for quoting references.